Resveratrol suppresses ethanol stress in winery and bottom brewery yeast by affecting superoxide dismutase, lipid peroxidation and fatty acid profile - Gharwalova, Lucia; Sigler, Karel; Dolezalova, Jana; Masak, Jan; Rezanka, Tomas; Kolouchova, Irena (World journal of microbiology & biotechnology, 2017)
Mid-exponential cultures of two traditional biotechnological yeast species, winery Saccharomyces cerevisiae and the less ethanol tolerant bottom-fermenting brewery Saccharomyces pastorianus, were exposed to different concentrations of added ethanol (3, 5 and 8%) The degree of ethanol-induced cell stress was assessed by measuring the cellular activity of superoxide dismutase (SOD), level of lipid peroxidation products, changes in cell lipid content and fatty acid profile. The resveratrol as an antioxidant was found to decrease the ethanol-induced rise of SOD activity and suppress the ethanol-induced decrease in cell lipids. A lower resveratrol concentration (0.5 mg/l) even reduced the extent of lipid peroxidation in cells. Resveratrol also alleviated ethanol-induced changes in cell lipid composition in both species by strongly enhancing the proportion of saturated fatty acids and contributing thereby to membrane stabilization. Lower resveratrol concentrations could thus diminish the negative effects of ethanol stress on yeast cells and improve their physiological state. These effects may be utilized to enhance yeast vitality in high-ethanol-producing fermentations or to increase the number of yeast generations in brewery.
Keywords: antioxidancia; superoxiddismutasa; Saccharomyces cerevisiae; mastné kyseliny; Wine; Ethanol stress; Resveratrol; Fatty Acids; metabolismus lipidů; Stress, Physiological; lipidy; stilbeny; Lipid peroxidation; Antioxidants; Stilbenes; Ethanol; ethanol; Lipid Metabolism; Yeast; peroxidace lipidů; resveratrol; Lipid Peroxidation; Lipids; Superoxide Dismutase; fyziologický stres; víno